Blood lead level is associated with non-alcoholic fatty liver disease in the Yangtze River Delta region of China in the context of rapid urbanization - Hualing Zhai; Chi Chen; Ningjian Wang; Yi Chen; Xiaomin Nie; Bing Han; Qin Li; Fangzhen Xia; Yingli Lu (BMC, 2017)
Abstract Background China has undergone rapid urbanization in the past three decades. We aimed to report blood lead level (B-Pb) in the most rapidly urbanized Yangtze River Delta Region of China, and explore the association B-Pb and non-alcoholic fatty liver disease (NAFLD). Methods Our data source was the SPECT-China study. We enrolled 2011 subjects from 6 villages in the Yangtze River Delta Region. Lead was measured by atomic absorption spectrometry. According to abdominal ultrasound, residents were divided into normal and NAFLD groups. Results In total, 824 (41.0%) were diagnosed with NAFLD. Medians (interquartile range) of B-Pb were 5.29 μg/dL (3.60-7.28) [0.25 μmol/L (0.17-0.35)] for men and 4.49 μg/dL (2.97-6.59) [0.22 μmol/L (0.14-0.32)] for women. In both genders, the NAFLD group had significantly greater B-Pb than normal group (both P < 0.001). The prevalence of NAFLD significantly increased with increasing B-Pb quartiles in men (P for trend = 0.032) and women (P for trend = 0.001). Residents in Shanghai had significantly greater B-Pb (P < 0.001) and a higher prevalence of NAFLD (P < 0.001). Compared with women in the lowest quartile of BLL, OR of NAFLD in women in the highest quartile was 1.613 (95%CI 1.082-2.405) (P for trend = 0.019) after multivariable adjustment. In men, this association showed marginal significance (OR 2.168, 95%CI 0.989-4.750, P for trend = 0.063). Conclusion B-Pb in Chinese residents in the Yangtze River Delta Region were much higher than in developed countries. Elevated B-Pb was associated with an increased risk of NAFLD, especially in women.